Prenatal Exposure to Androgen Excess Increases LH Pulse Amplitude During Postnatal Life in Male Sheep - Recabarren, S. E.; Recabarren, M.; Rojas-Garcia, P. P.; Cordero, M.; Reyes, C.; Sir-Petermann, T. (Hormone and Metabolic Research, 2012)
Prenatal exposure to excess testosterone has a profound impact on reproductive and metabolic functions in young and adult female sheep. Nevertheless, few studies have addressed the impact of prenatal exposure to an excess of androgens on reproductive and metabolic functions in males. The aim of the present study was to assess the impact of prenatal exposure to an excess of testosterone or dihydrotestosterone on the luteinizing hormone (LH) pulse characteristics during sexual development in male sheep. Control male sheep (C-males) and males born to mothers exposed to twice weekly injections of 30 mg testosterone or dihydrotestosterone from day 30–90 and 40 mg from day 90–120 of gestation (T-males, DHT-males) were studied at 5, 10, and 20 weeks of age, ages that represent infancy, early prepubertal, and late prepubertal stages of sexual development in this species, respectively. Patterns of LH pulsatility showed that T- and DHT-males exhibited a higher secretion of LH during the 6-h study and a higher amplitude of the LH pulses compared with C-males. Moreover, nadir of the pulses was higher in T- and DHT-males compared with C-males. Frequency of LH pulses, however, was not different within ages or between groups. These results show that males can be responsive to prenatal androgenization and suggest that treatment transiently alters the amplitude of LH pulses probably as the result of defects in the pituitary responsiveness pattern or in the gonadotropin-releasing hormone (GnRH) release pattern.
Keywords: androgen; gonadotropin; polycystic ovary syndrome; testes; anterior pituitary; fetal programming